Penggunaan Metode ABA untuk Mengenalkan Huruf Hijaiyah pada Anak Autisme di Yayasan Sahabat Rakyat Sejahtera Bengkulu Utara - Nur Ratih Arifah; Rohimin Rohimin; Nelly Marhayati (Journal on Education, 2023)
The purpose of this study was to find out how to use the ABA (Applied Behavior Analysis) method to introduce hijaiyah letters to autistic children aged 4-6 years at the Sahabat Rakyat Sejahtera Foundation, North Bengkulu. This study uses a qualitative approach with a type of field research (field research). Collecting data using observation techniques, interviews and documentation. This study concludes that 1. The use of the ABA method at the Friends of the Prosperous People's Association uses three techniques, namely matching, identification and imitation techniques. 2. The inhibiting factor in the application of this method is that students often have tantrums, lose focus and even cry non-stop. Tantrums occur because students do not get what they want, therefore if a tantrum occurs, the therapist immediately gives what students want or like. This is proven to make students calmer. The supporting factor is the ability of students to understand learning. By applying learning while playing it turns out to be very influential on students. When one program is successful, students are allowed to play after playing, students learn again to continue other programs, it turns out that this can increase student focus. Another supporting factor is the support from the parents of the students at the North Bengkulu Prosperous People's Friends Foundation.